Analisis Keputusan Anggota Memilih Produk Tabungan Tabah Di Baitul Maal Wat Tamwil Nuansa Umat Jawa Timur Cabang Sumbersari Jember - Della Nur Maulidya; Lidya Yuli Ambarwati; Nadilla Retno Anjani; Ahmad Fauzi (CV. ITTC INDONESIA, 2024)
Tabah savings (mudharabah) is a fundraising product that is in great demand by the community at KSPPS BMT NU East Java Sumbersari Branch, Jember Regency. In this savings, members get a competitive ratio and withdrawals can be made at any time. Achievement of the target on savings products tabah greatly increased in each month. Each prospective saver has its own decision in choosing a savings product tabah. This study aims to determine how the customer's decision in choosing tabah savings products (mudharabah) at KSPPS BMT NU East Java Sumbersari Branch Jember Regency. In this study using descriptive qualitative research methods. data analysis approach obtained by providing exposure or description of the situation and conditions studied. The results of this study state that the member's decision to choose a savings product is very appropriate because it is in accordance with the needs of the community.